Financial Resource Provision and Utilization in Basic Education in Nigeria: Problems and Prospects - Uduak Imo , Ekpoh; Michael Ekpenyong, Asuquo (International Journal of Educational Management, 2025)
Adequate provision of financial resource and its subsequent utilization has always been at the forefront of laudable educational programme implementation. Education is an instrument par excellence for the development of the individual and the country as a whole. For the foundation of education to be properly laid, attention of educational stakeholders must be drawn to Basic Education, because it is at this p oint that intellectual development of every learner begins, when compared with other higher (secondary and tertiary) levels of education. There is therefore no d oubt that a learner would not be successful at any succeeding level of education when such a learner did not have the proper foundation at the Basic Education level. Basic Education is the cradle for the development of a total person, to be useful to himself or herself and the society at large. Notwithstanding the commendable goals and objectives of Basic Education programme, the achievement of its goals and objectives appears to be hampered by many problems due to inadequate provision of f unds and poor utilization of educational financial resources. The article therefore discussed the concept of financial provision and utilization, concept of Basic E ducation, sources of financing Basic Education, utilization of financial resources at Basic Education level, problems/challenges in financing Basic Education in Nigeria, prospects of financing basic education and the way forward with respect to ameliorating problems of. Basic Education financing.